1992
DOI: 10.1159/000284772
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Schneider’s First Rank Symptoms for Schizophrenia in Malay Patients

Abstract: The frequency of Schneider’s first rank symptoms (FRS) was studied in 221 Malay patients with functional psychosis. The prevalence of FRS in schizophrenia was 26.7%. The most common symptoms were voice arguing, passivity phenomena and somatic passivity. In the absence of organic brain dysfunction, the specificity of FRS for schizophrenia was 87.8%, and their positive predictive value was 90.6%. These findings indicate that although FRS is not pathognomonic of schizophrenia, their presence should be regarded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although it is now questioned whether fi rst rank symptoms are reliably diagnostic [4] , such experiences remain a common theme, with studies reporting their prevalence of anything between 27 [5] and 73% [6] in schizophrenia.…”
mentioning
confidence: 99%
“…Although it is now questioned whether fi rst rank symptoms are reliably diagnostic [4] , such experiences remain a common theme, with studies reporting their prevalence of anything between 27 [5] and 73% [6] in schizophrenia.…”
mentioning
confidence: 99%
“…FRS were present in 35% in India,[25] 25% in Sri Lanka,[26] and 27% in Malaysia. [27] In contrast, a study from Nigeria reported 60.3% FRS. [28] In the ISPS, Nigeria and Ghana had higher frequency of FRS than the other developing countries.…”
Section: Cultural Influence On Phenomenologymentioning
confidence: 98%
“…However, reliability between study centers was still highly variable (r=0.37 to 0.95) (Wing and Nixon, 1975). Determining the prevalence of FRAH in schizophrenia has also been problematic, with estimates ranging from 10–40% for RC, 0–34% for VC, and 22–48% for cases with at least one FRAH (Ahmed and Naeem, 1984; Bland and Orn, 1980; Carpenter and Strauss, 1974; Chandrasena and Rodrigo, 1979; Gureje and Bamgboye, 1987; Lewine et al, 1982; Malik et al, 1990; Marneros, 1984; Mellor, 1970; Peralta and Cuesta, 1999; Salleh, 1992; Shinn et al, 2011; Thorup et al, 2007; Zarrouk, 1978). The variations in FRAH estimates may reflect different clinical and cultural contexts (Chandrasena, 1987), but also may be due to the variable use of narrow or wide interpretations of FRAH (Koehler, 1979; O’Grady, 1990), as well as the use of different diagnostic criteria for schizophrenia when determining FRAH base rates (Nordgaard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%